BEAVRS full core burnup calculation in hot full power condition by RMC code. (March 2017) - Liu, Shichang; Liang, Jingang; Wu, Qu; Guo, JuanJuan; Huang, Shanfang; Tang, Xiao; Li, Zeguang; Wang, Kan
Highlights: TMS and thermal scattering interpolation were developed to treat cross sections OTF. Hybrid coupling system was developed for HFP burnup calculation of BEAVRS benchmark. Domain decomposition was applied to handle memory problem of full core burnup. Critical boron concentration with burnup by RMC agrees with the benchmark results. RMC is capable of multi-physics coupling for simulations of nuclear reactors in HFP. Abstract: Monte Carlo method can provide high fidelity neutronics analysis of different types of nuclear reactors, owing to its advantages of the flexible geometry modeling and the use of continuous-energy nuclear cross sections. However, nuclear reactors are complex systems with multi-physics interacting and coupling. MC codes can couple with depletion solver and thermal-hydraulics (T/H) codes simultaneously for the "transport-burnup-thermal-hydraulics" coupling calculations. MIT BEAVRS is a typical "transport-burnup-thermal-hydraulics" coupling benchmark. In this paper, RMC was coupled with sub-channel code COBRA, equipped with on-the-fly temperature-dependent cross section treatment and large-scale detailed burnup calculation based on domain decomposition. Then RMC was applied to the full core burnup calculations of BEAVRS benchmark in hot full power (HFP) condition. The numerical tests show that domain decomposition method can achieve the consistent results compared with original version of RMC while enlarging the computational burnup regions. The results of HFP by RMC agree well with the reference values of BEAVRS benchmark and also agree well with those of MC21. This work proves the feasibility and accuracy of RMC in multi-physics coupling and lifecycle simulations of nuclear reactors.